Strategic use of straw as environmental enrichment for prepartum sows in farrowing crates - Martins, Renata Aparecida; Caldara, Fabiana Ribeiro; Crone, Carla; Odakura, Agnes Markiy; Bevilacqua, Augusto; Nieto, Viviane Maria Oliveira dos Santos; Felix, Gisele Aparecida; Santos, Alessandra Pereira dos; Santos, Luan Sousa dos; Garcia, Rodrigo Garofallo; Lippi, Isabella Cristina de Castro [UNESP] (Elsevier B.V., 2021)
Sows are highly motivated to build a nest prior to farrowing, but, given the barren environment of farrowing crates, this behaviour is limited and improperly expressed. We aimed to assess the effects of a straw provision in the farrowing crate as environmental enrichment in the prepartum period on: 1) sows' reproductive and behavioural responses before, during and after farrowing, and 2) piglets' performance during lactation. Multiparous sows (N = 32) were assigned according to parity to two enrichment conditions: 1) Control sows, and 2) Straw sows, (N = 16 sows/treatment). In the control treatment, the sows were kept in farrowing crates with no environmental enrichment. In the straw treatment, straw was provided in the farrowing crate by purpose-built boxes attached to the crate bars next to the sows. Straw was provided 24 h prior to the expected due date and removed after farrowing. Sows' behaviours (N = 12 sows/treatment) were recorded uninterruptedly from 12 h prior to farrowing until the 13th day of lactation. Data on reproductive performance (number of liveborn and stillborns, farrowing duration, and births interval) were collected. Five piglets were selected from each sow for assessment of performance and levels of blood lactate. All piglet deaths, as well as their causes, were recorded. Sows from straw treatment exhibited a higher frequency of nest-building behaviour and lower frequency of stereotyped behaviour and sitting posture (P < 0.05). No differences were found in the sows' behaviours during farrowing (P > 0.05). The sows from control treatment exhibited a higher number of posture changes (P = 0.057). The frequency of nursing was higher in the sows that had access to straw (P < 0.05). No differences were observed in reproductive performance (P> 0.05). Providing straw had no effects on performance, lactate levels, or postnatal mortality of piglets (P > 0.05). Providing nesting material in the farrowing crate improves the welfare of sows by increasing their motivation to build the nest and reducing the stereotyped behaviours prior to farrowing. Moreover, access to straw reduces sow unrest during farrowing and stimulates the maternal behaviour of nursing.
Keywords: Hypoxia; Lactate; Nest-building behaviour; Reproductive performance; Stereotypy